Analisis Kepuasan Pelanggan Kopi Kapal Api Menggunakan Metode Net Promoter Score - Komharudin, Komharudin; Umami, Nida Auliana; Hidayatulloh, Khairil (Program Studi Sistem Informasi Akuntansi Kampus Kota Sukabumi, 2025)
This study aims to measure the level of customer satisfaction and customer loyalty of Kapal Api Coffee products launched by Digital Business Students as a Final Exam in the Costumer Behavior course which is a Study Program from Sukabumi Polytechnic which is about understanding how, why, and when consumers make decisions to buy a product or service. This research was conducted on customers of Kapal Api Coffee which aims to calculate the level of satisfaction where the results can be used as a basis for future development. Data collection for this research is through questionnaires distributed to customers. To determine the probability of consumer satisfaction, a customer satisfaction analysis is carried out using the Net Promoter Score (NPS) method.